PSYCHO-DEMOGRAPHIC FACTORS AS CORRELATES OF TEACHER EFFECTIVENESS IN SECONDARY SCHOOLS IN LAGOS- STATE, NIGERIA (2014)
The importance of teacher effectiveness cannot be over emphasised, as it is linked to learning outcomes and socially desirable behaviour among students. Besides, it is one of the indices through which quality assurance is ascertained in education. Literature has shown that the combination of certain psycho-demographic factors such as teacher personality, self efficacy, self esteem, gender and work experience have link with teacher effectiveness. However, most studies on teacher effectiveness have examined separately the effects of these factors without adequate attention on their combined effects. This study, therefore, investigated the psycho-demographic (self-efficacy, self-esteem, locus of control, work experience, gender and personality) factors as correlates of teacher effectiveness in secondary schools in Lagos State, Nigeria. The study adopted the descriptive survey research design. The multi-stage sampling technique was used to select 574 Junior Secondary School teachers from six education districts in Lagos State. Five instruments were used: Teacher Effectiveness Questionnaire with three sub-scales (Teacher Self-reported version r=0.76; Student Reported Version r=0.73; and Head of Unit/Principal Reported Version r=0.71); Teacher Self-efficacy Scale (r=0.62); Self-esteem Scale (r=0.84); Teacher Locus of Control Scale (r=0.61), and NEO-five Factor Inventory (r=0.79). Six research questions were answered and two hypotheses tested at 0.05 level of significance. Data were analysed using descriptive statistics, Pearson Product Moment Correlation and Multiple Regression. There was a significant joint effect of independent variables (self-esteem, self-efficacy, locus of control, gender and work experience) on teacher effectiveness (F(8,501)= 3.59, p<0.05); and a significant relative effect in this order of magnitude: teacher's self-esteem (?=0.10, t=2.27, p<0.05); self-efficacy (?=0.09, t=1.97, p<0.05); locus of control (?=0.08, t=1.63, p>0.05); gender (?=-0.05, t=1.05, p>0.05), and work experience (?=0.04, t=0.82, p>0.05). The results further showed that self-efficacy (r=0.12, p<0.05) and locus of control (r=0.09, p<0.05) had significant relationship with teacher effectiveness. Work experience, gender and extroversion however, did not show significant influence on teacher effectiveness. Self-efficacy impacted on teacher level of effectiveness, whereas work experience, gender, and extroversion did not show predictable influence on their effectiveness. There was also significant joint effect of teacher personality factors (openness to experience, conscientiousness, neuroticism, extroversion and agreeableness) on teacher effectiveness (F (5,504)=16.42, p<0.05); and a significant relative effect in this order of magnitude: openness (?=0.54, t=4.97, p<0.05); conscientiousness (?= -0.62, t=5.70, p<0.05); neuroticism (?=-0.38, t=4.75, p<0.05); extroversion ?=0.11, t=1.96, p<0.05) and agreeableness (? =-0.04, t=0.07, p>0.05). The results also showed that openness to experience (r=0.15, p<0.05), agreeableness (r=-0.11, p<0.05), neuroticism (r=-0.20, p<0.05), and conscientiousness (r=-0.20, p<0.05) had significant relationship with teacher effectiveness. Teacher personality, self efficacy and locus of control are crucial to teacher effectiveness. Thus secondary school teachers in Lagos state should be made to go through meta-cognitive and self regulation training in other to enhance their level of effectiveness, with a view to enhancing students' general performance.